Targeted mutagenesis on PDGFRα-Fc identifies amino acid modifications that allow efficient inhibition of HCMV infection while abolishing PDGF sequestration. - Svenja Feldmann; Immanuel Grimm; Dagmar Stöhr; Chiara Antonini; Peter Lischka; Christian Sinzger; Cora Stegmann (PLoS Pathogens)
Platelet-derived growth factor receptor alpha (PDGFRα) serves as an entry receptor for the human cytomegalovirus (HCMV), and soluble PDGFRα-Fc can neutralize HCMV at a half-maximal effective concentration (EC50) of about 10 ng/ml. While this indicates a potential for usage as an HCMV entry inhibitor PDGFRα-Fc can also bind the physiological ligands of PDGFRα (PDGFs), which likely interferes with the respective signaling pathways and represents a potential source of side effects. Therefore, we tested the hypothesis that interference with PDGF signaling can be prevented by mutations in PDGFRα-Fc or combinations thereof, without losing the inhibitory potential for HCMV. To this aim, a targeted mutagenesis approach was chosen. The mutations were quantitatively tested in biological assays for interference with PDGF-dependent signaling as well as inhibition of HCMV infection and biochemically for reduced affinity to PDGF-BB, facilitating quantification of PDGFRα-Fc selectivity for HCMV inhibition. Mutation of Ile 139 to Glu and Tyr 206 to Ser strongly reduced the affinity for PDGF-BB and hence interference with PDGF-dependent signaling. Inhibition of HCMV infection was less affected, thus increasing the selectivity by factor 4 and 8, respectively. Surprisingly, the combination of these mutations had an additive effect on binding of PDGF-BB but not on inhibition of HCMV, resulting in a synergistic 260fold increase of selectivity. In addition, a recently reported mutation, Val 242 to Lys, was included in the analysis. PDGFRα-Fc with this mutation was fully effective at blocking HCMV entry and had a drastically reduced affinity for PDGF-BB. Combining Val 242 to Lys with Ile 139 to Glu and/or Tyr 206 to Ser further reduced PDGF ligand binding beyond detection. In conclusion, this targeted mutagenesis approach identified combinations of mutations in PDGFRα-Fc that prevent interference with PDGF-BB but maintain inhibition of HCMV, which qualifies such mutants as candidates for the development of HCMV entry inhibitors.